Bonding behavior of interface between reinforced concrete after fire and carbon fiber-reinforced polymer. (13th June 2023) - Mar Swe, Than; Limpaninlachat, Pornpen; Daungwilailuk, Totsawat; Pansuk, Withit; Pheinsusom, Phoonsak
Highlights: Bonding performance between fired concrete and CFRP plate was investigated. Fire exposure significantly affected bond strength and effective bond length. The predicted model of interfacial fracture energy was proposed. Shear stress-slip model was introduced regarding the strain-slip relationship. Abstract: This study aims to investigate the bonding behavior between the fire-damaged concrete specimens strengthened by Carbon Fiber Reinforced Polymer (CFRP) plate. Twenty-five sets of damaged concrete specimens with variable concrete covering and exposure time conformed to ASTM E119 were prepared and bonded with CFRP plates with different bond lengths. According to Modified pull-out tests, with increasing the fire exposure time to 45 and 90 min, it significantly reduced the interfacial bonding strength and ductility. The bonding performance of fired specimens is achieved by applying longer bond length. Finally, the shear stress–slip model of the fire-damaged concrete bonded with CFRP can be proposed by using the experimental relationship between strain and slip with the simple derivative of local shear–stress equilibrium. While the effect of parameters are included in this model through the predicted interfacial fracture energy.